Geotechnical aspects of offshore wind turbine dynamics from 3D non-linear soil-structure simulations. Issue 120 (May 2019) - Kementzetzidis, Evangelos; Corciulo, Simone; Versteijlen, Willem G.; Pisanò, Federico
Abstract: The development of the offshore wind industry is motivating substantial research efforts worldwide, where offshore wind turbines (OWTs) of increasing size are being installed in deeper water depths. Foundation design is a major factor affecting the structural performance of OWTs, with most installations founded to date on large-diameter monopiles. This work promotes advanced 3D finite element (FE) modelling for the dynamic analysis of OWT-monopile-soil systems. A detailed FE model of a state-of-the-art 8 MW OWT is analysed by accounting for dynamic soil-monopile interaction in presence of pore pressure effects. For this purpose, the critical-state, bounding surface SANISAND model is adopted to reproduce the hydro-mechanical cyclic response of the sand deposit. The response to realistic environmental loading histories (10 min duration) are simulated, then followed by numerical rotor-stop tests for global damping estimation. While linking to existing literature, all FE results are critically inspected to gain insight relevant to geotechnical design. The modelling tools adopted (i) support the robustness of 'soft-stiff' foundation design with respect to natural frequency shifts, even during severe storm events; (ii) provide values of foundation damping in line with field measurements; (iii) suggest that pore pressure effects might more likely affect soil-monopile interaction under weak-to-moderate environmental loading. Abstract : Highlights: The non-linear﻿ dynamic response of offshore wind turbines is studied through 3D FE simulations. Dynamic soil-monopile ﻿interaction is explored using﻿ an advanced plasticity model. The robustness of current design practice with respect to natural frequency drops is assessed. The interplay of loading conditions﻿ and permeability is studied﻿ in relation to global damping.